Cyst Fluid Carcinoembryonic Antigen Level Difference between Mucinous Cystic Neoplasms and Intraductal Papillary Mucinous Neoplasms - Ibrahim Hakkı Köker (Clinical Endoscopy, 2021)
Background/Aims The role of cyst fluid carcinoembryonic antigen (CEA) level in differentiating mucinous pancreatic cystic lesions (PCLs) is controversial. We investigated the role of cyst fluid CEA in differentiating low-risk (LR)-intraductal papillary mucinous neoplasms (IPMNs) from high-risk (HR)-IPMNs and LR-mucinous cystic neoplasms (MCNs). Methods This was a retrospective study of 466 patients with PCLs who underwent endoscopic ultrasound-guided fine-needleaspiration over a 7-year period. On histology, low-grade dysplasia and intermediate-grade dysplasia were considered LR, whereas high-grade dysplasia and invasive carcinoma were considered HR. Results Data on cyst fluid CEA levels were available for 50/102 mucinous PCLs with definitive diagnoses. The median CEA (range) levels were significantly higher in HR cysts than in LR cysts (2,624 [0.5–266,510] ng/mL vs. 100 [16.8–53,445]ng/mL, p=0.0012). The area under the receiver operating characteristic curve (AUROC) was 0.930 (95% confidence interval [CI], 0.5–0.8; p<0.001) for differentiating LR-IPMNs from LR-MCNs. The AUROC was 0.921 (95% CI, 0.823–1.000; p<0.001) for differentiating LR-IPMNs from HR-IPMNs. Both had a CEA cutoff level of >100ng/mL, with a negative predictive value (NPV) of 100%. Conclusions Cyst fluid CEA levels significantly vary between LR-IPMNs, LR-MCNs, and HR-IPMNs. A CEA cutoff level of >100ng/mL had a 100% NPV in differentiating LR-IPMNs from LR-MCNs and HR-IPMNs.